Design and implementation of a predictive digital position control system for a DC Motor subject to non-linear loads - Benites Saravia, Raúl (2001)
This work presents the behavior of Model-Based Predictive Control (MBPC), aimed at controlling a SISO process. The process is a non-linear system, to which after linearizing and discretizing, predictive control techniques are applied. The nonlinear process (plant) consists of a DC servomotor with reduction, a power stage and a rod coupled to the motor rotor. Use is made of a LAB-PC+ interface card (implemented in a Pentium microcomputer) and an auxiliary interface. The software used for the simulation is MATLAB and the one used for the implementation of the position control algorithm is the C language. The results presented are in real time. For reasons of space Simulations have not been presented in this article.